Isentropic zonal average formalism and the near-surface circulation - Koh, Tieh Yong (2014)
Hoskins (1991) proposed dividing the atmosphere into 3 regions: Overworld, Middleworld and Underworld, using potential temperature θ and potential vorticity (PV) as reference (Fig. 1). In the Underworld (θ < 300 K), isentropes intercept the Earth’s surface and a direct isentropic zonal average circulation exists in the mid-latitudes. Held and Schneider (1999) suggested that this circulation may be understood as follows: the equator-pole temperature gradient determines the near-surface eddy heat flux via an eddydiffusion mechanism. The poleward eddy heat flux in turn drives an equatorward mean flow next to the surface whose horizontal convergence in the subtropics forces the mean quasi-isentropic ascent of air into the troposphere. Radiative cooling causes air to sink back to the surface, thus closing the circulation.